The Impact of Green Products on the Performance and Sustainabiity of Small and Medium Enterprises in Abuja, Nigeria - Marcus Garvey Orji; Hadiza Abubakar Ahmad; Abdullahi Dangana (Britain International for Academic Research (BIAR) Publisher, 2025)
The objective of this study was to assess the impacts of Green Products on the performance and sustainability of Small and Medium Enterprise (SMEs) in Abuja, the study was survey research sampling the opinion of 322 respondents within Abuja Municipal Area Council. Their opinion was collected using a structured questionnaire. The data obtained was analysed using descriptive and inferential statistics, and the hypothesis was tested by means of correlation and regression analysis. The findings of the study reveals that the impact of green product on the performance and sustainability of Small and Medium Business Enterprises is strong with R-value of 0.684 and a p-value of 0.000 which is lesser than the cut off significant level of 5%, also the 48.1% explanatory power implies that any effort to enhance green product will likely lead to a notable increase on the performance and sustainability of Small and Medium Enterprises, The finding of this study leads to conclusion and lends further support to the assumptions that green product development and marketing practices has emerged as a powerful tool that transcends profit considerations. It is a strategic marketing imperative that aligns businesses with the principles of sustainable development in line with SDG 12 (Responsible consumption and production). Therefore, the study recommended among others, that there is the need for small and medium enterprises in Abuja to intensify the integration of eco-friendly technologies and practices in their production and products make ups such as recycling and reusing technologies to enhance their business performance. Equally, Small and medium enterprises owners or operators in Abuja should intensify efforts to promote environmentally responsible ways of operating a business by ensuring that their operations are respectful of the Planetary boundaries; and showcase the dedication to improve operations while meeting certain environmental, social, and governance requirements in line with sustainable development goals Agenda 2030 of United Nations.